Obesity Does not Compromise Ovarian Reserve Markers in Infertile Women - Gorkem, Umit; Kucukler, Ferit Kerim; Togrul, Cihan; Gulen, Şebnem (Geburtshilfe und Frauenheilkunde, 2019)
Introduction In the literature, conflicting results from studies examining the relationship between obesity and ovarian reserve have been reported. The purpose of the study is to investigate whether obesity adversely affects serum concentrations of ovarian reserve markers in infertile women with different ovarian reserve status.Materials and Methods A total of 402 women were assigned to three groups according to body mass index (BMI; < 25 kg/m2: normal, n = 198; 25.0 – 29.9 kg/m2: overweight, n = 126; and ≥ 30 kg/m2: obese, n = 78). The women were also divided into two groups according to waist circumference (WC; < 80 cm: normal, n = 103; and ≥ 80 cm: obese, n = 299). Participants were also categorized into three types of ovarian reserve patterns: normal (n = 146), high (n = 112), and poor ovarian reserve (n = 144). The serum anti-Mullerian hormone (AMH), estradiol (E2), and follicle-stimulating hormone (FSH) levels were assayed and compared in all groups.Results There were no significant differences in BMI and WC in the three ovarian reserve groups. There were significant differences between all ovarian reserve groups for AMH, E2, and FSH (p < 0.001 for all). The comparisons of ovarian reserve parameters (AMH, E2, and FSH) and obesity parameters (BMI and WC) revealed no significant differences in women with all ovarian reserve patterns.Conclusion The parameters of ovarian reserve do not seem to be affected by increased BMI and WC. Thus, AMH may be considered as a reliable marker of ovarian reserve.
Keywords: obesity; body mass index; waist circumference; ovarian reserve